The accuracy of computerised cephalometric analysis compared to conventional manual method (Mustansiria Dental Journal, 2005)
Computerised eephalometric softwares are widely spreading nowadays withseveral options regarding orthodontists demands. This study aims to compare theaccuracy of the computerised procedure from digitising the radiograph to the finalcephalometric analysis. Twenty—six lateral cephalograms were analysed, thirteenlandmarks were permanently marked and traced and eighteen variables; nine anglesand nine lines in both horizontal (X) and vertical (Y) directions were measuredmanually first, then scanned and the same landmarks were digitised on—screen usingViewbox 3.0.l cephalometric computer sottware. The results show that computerisedangular measurements were more comparable to the manual method than with linearmeasurements, with most of the differences being of low clinical importance